Zr-Ti-Mo-Nb-Al alloy and preparation method thereof
By adjusting the components and phase composition of Zr-Ti-Mo-Nb-Al alloy, a high-strength and high-plastic BCC and B2 phase structure is formed, the problem of insufficient strength and plasticity of existing high-temperature alloys at high temperatures is solved, and the problem of insufficient strength and plasticity of existing high-temperature alloys is realized. The high performance and low density characteristics of the alloy are suitable for aerospace.
Patent Information
- Application Number
- CN202411450433.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-14
AI Technical Summary
The existing high-temperature alloys have shortcomings in strength and plasticity at high temperatures, which are difficult to meet the high-temperature mechanical performance requirements in the aerospace field, and are too high in density and have relatively low cost performance.
Using Zr-Ti-Mo-Nb-Al alloy, the mass percentage of Ti, Mo, Nb, and Al is adjusted to form a BCC matrix and a high-strength B2 phase, which improves the strength and plasticity of the alloy, and reduces the thermal isostatic pressure treatment. density.
The high strength and good plasticity of Zr-Ti-Mo-Nb-Al alloy are achieved, the room temperature yield strength reaches 1600~1800MPa, the dynamic compression compressive strength is 2400~2800MPa, and the density is reduced to 5.686g/cm3, which is suitable for high-temperature applications.
Smart Images

Figure CN119307784A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of high temperature alloys, and in particular to a Zr-Ti-Mo-Nb-Al alloy and a preparation method thereof. Background Art
[0002] High-temperature alloy refers to a type of metal material based on iron, nickel and cobalt, which can work for a long time at high temperatures above 600°C and under certain stress. It has excellent high-temperature strength, good oxidation resistance and thermal corrosion resistance, good fatigue performance, fracture toughness and other comprehensive properties. It is also called "superalloy" and is mainly used in the aerospace and energy fields. Among them, the use temperature of iron-based high-temperature alloys can generally only reach 750-780°C, the use temperature of cobalt-based high-temperature alloys is generally 600-1000°C, and the maximum melting point of nickel-based high-temperature alloys is limited to about 1350°C. However, with the increase in heat conversion efficiency, the requirements for the mechanical properties of high-temperature alloys in the hot end components such as the combustion chamber, turbine working blades and turbine disks of coal-fired gas turbines are constantly increasing. The temperature of the gas sprayed onto the blades exceeds 1300°C, and traditional high-temperature resistant alloys are difficult to adapt to such high service temperatures. Therefore, a Zr-Ti series multi-element alloy with better high-temperature resistance is proposed.
[0003] At present, high entropy alloys composed of high melting point metals such as Zr, Ti, Mo, Nb, Ta, Hf, Cr, W, and V are called refractory high entropy alloys. Compared with traditional high-temperature alloys, refractory high entropy alloys have higher high-temperature strength, high-temperature oxidation resistance, and high-temperature phase stability. However, the organization of refractory high entropy alloys is mostly a single BCC phase structure, which is not conducive to further improvement of high-temperature strength resistance. In addition, the density of such alloys is too high and the specific strength is low, so the cost performance is low when used in the aerospace field. In addition, refractory high entropy alloys also have the problem of poor room temperature plasticity. For example, MoNbTaW and MoNbTaWV alloys have a single-phase BCC structure. At 1600°C, the yield strength of the two alloys can still be maintained above 400MPa, but the plasticity at room temperature is less than 2%. Summary of the invention
[0004] The object of the present invention is to provide a Zr-Ti-Mo-Nb-Al alloy and a preparation method thereof. The Zr-Ti-Mo-Nb-Al alloy provided by the present invention has low density, high strength and good plasticity.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The invention provides a Zr-Ti-Mo-Nb-Al alloy, wherein the components are calculated by mass percentage as follows: Ti 20-30%, Mo 3-8%, Nb 3-8%, Al 2-8% and the balance Zr.
[0007] Preferably, the components are calculated by mass percentage as follows: Ti 24-28%, Mo 4-6%, Nb 4-6%, Al 3-7% and the balance Zr.
[0008] Preferably, the phase composition of the Zr-Ti-Mo-Nb-Al alloy includes a BCC phase and a B2 phase dispersed in the BCC phase.
[0009] Preferably, the phase composition of the Zr-Ti-Mo-Nb-Al alloy comprises, by volume percentage, 60-65% BCC phase and 35-40% B2 phase.
[0010] The present invention also provides a method for preparing the Zr-Ti-Mo-Nb-Al alloy described in the above technical solution, comprising the following steps:
[0011] After the alloy raw materials are mixed, they are melted and hot isostatically pressed in sequence to obtain a Zr-Ti-Mo-Nb-Al alloy.
[0012] Preferably, the alloy raw materials include sponge titanium, sponge zirconium, Al-Mo master alloy and Al-Nb master alloy.
[0013] Preferably, the smelting includes vacuum consumable arc melting and vacuum consumable shell melting performed sequentially.
[0014] Preferably, the temperature of the vacuum consumable arc melting is 1700-1900° C., and the time of the vacuum consumable arc melting is 5-8 minutes.
[0015] Preferably, the power of the vacuum consumable shell smelting is 200-250 kW, and the time of the vacuum consumable shell smelting is 5-8 min.
[0016] Preferably, the temperature of the hot isostatic pressing is 700-750° C., the pressure of the hot isostatic pressing is 100-140 MPa, and the time of the hot isostatic pressing is 2-2.5 h.
[0017] Preferably, the smelting, secondary smelting and hot isostatic pressing are all carried out under an argon atmosphere.
[0018] The present invention provides a Zr-Ti-Mo-Nb-Al alloy, wherein the components are calculated by mass percentage as follows: Ti 20-30%, Mo 3-8%, Nb 3-8%, Al 2-8% and the balance Zr. The present invention utilizes Zr, Ti, Mo, Nb and Al to form a BCC matrix, wherein Al and Zr form a high-strength and high-hardness B2 phase, thereby improving the strength of the Zr-Ti-Mo-Nb-Al alloy; by controlling the mass percentage of Ti, Mo and Nb, and combining with Al to regulate the proportion of the plastic BCC phase and the high-strength B2 phase, the strength and plasticity of the Zr-Ti-Mo-Nb-Al alloy are improved, while reducing the alloy density. The results of the embodiment show that the room temperature quasi-static compressive yield strength of the Zr-Ti-Mo-Nb-Al alloy prepared by the present invention is 1600-1800 MPa, and the compression failure strain is 15-17%; the room temperature dynamic compressive strength is 2400-2800 MPa, and the compression failure strain is 3-4%; the density can be as low as 5.686 g / cm 3 . BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 The XRD pattern of the Zr-Ti-Mo-Nb-Al alloy prepared in Example 1 of the present invention;
[0020] Figure 2 This is a SEM backscatter image of the Zr-Ti-Mo-Nb-Al alloy prepared in Example 1 of the present invention at a magnification of 200 times;
[0021] Figure 3 This is a SEM backscatter image of the Zr-Ti-Mo-Nb-Al alloy prepared in Example 1 of the present invention at a magnification of 30,000 times;
[0022] Figure 4 The room temperature quasi-static compressive stress-strain curve of the Zr-Ti-Mo-Nb-Al alloy prepared in Example 1 of the present invention;
[0023] Figure 5 This is the room temperature dynamic compressive stress-strain curve of the Zr-Ti-Mo-Nb-Al alloy prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0024] The invention provides a Zr-Ti-Mo-Nb-Al alloy, wherein the components are calculated by mass percentage as follows: Ti 20-30%, Mo 3-8%, Nb 3-8%, Al 2-8% and the balance Zr.
[0025] In the present invention, the components of the Zr-Ti-Mo-Nb-Al alloy include 20-30% Ti, preferably 24-28%, and more preferably 26% Ti by mass percentage. The present invention further ensures that Ti and other alloy elements combine with Al to form a plastic BCC phase by limiting the content of Ti, thereby increasing the plasticity of the Zr-Ti-Mo-Nb-Al alloy.
[0026] In the present invention, the components of the Zr-Ti-Mo-Nb-Al alloy include 3-8%, preferably 4-6%, and more preferably 5% Mo by mass percentage. The present invention further ensures that Mo and other alloy elements can form a plastic BCC phase in combination with Al by limiting the content of Mo, thereby increasing the plasticity of the Zr-Ti-Mo-Nb-Al alloy.
[0027] In the present invention, the components of the Zr-Ti-Mo-Nb-Al alloy include 3-8%, preferably 4-6%, and more preferably 5% Nb by mass percentage. The present invention further ensures that Nb and other alloy elements can form a plastic BCC phase in combination with Al by limiting the content of Nb, thereby increasing the plasticity of the Zr-Ti-Mo-Nb-Al alloy.
[0028] In the present invention, the components of the Zr-Ti-Mo-Nb-Al alloy include Al2-8%, preferably 4-6%, and more preferably 5%, by mass percentage. The present invention further ensures that Al can fully combine with Ti, Mo, and Nb to form a BCC phase by limiting the content of Al, and further ensures that Al can fully combine with Zr to form a B2 phase, thereby increasing the plasticity and strength of the Zr-Ti-Mo-Nb-Al alloy; and reducing the density of the Zr-Ti-Mo-Nb-Al alloy, further improving the specific strength of the Zr-Ti-Mo-Nb-Al alloy.
[0029] In the present invention, the composition of the Zr-Ti-Mo-Nb-Al alloy includes a balance of Zr by mass percentage. The present invention further ensures that Zr can fully combine with Al to form a B2 phase by limiting the content of Zr, thereby improving the strength of the Zr-Ti-Mo-Nb-Al alloy.
[0030] In the present invention, the components of the Zr-Ti-Mo-Nb-Al alloy are preferably Ti 24-28%, Mo 4-6%, Nb 4-6%, Al 3-7% and the balance Zr in terms of mass percentage. The present invention limits the mass percentage of each component of the Zr-Ti-Mo-Nb-Al alloy so that Zr is more fully combined with Al, Ti, Mo and Nb to form a BCC phase, and Al can be combined with Zr to form a B2 phase, thereby further increasing the plasticity and strength of the Zr-Ti-Mo-Nb-Al alloy.
[0031] In the present invention, the phase composition of the Zr-Ti-Mo-Nb-Al alloy preferably includes a BCC phase and a B2 phase dispersed in the BCC phase. The present invention can increase the plasticity of the Zr-Ti-Mo-Nb-Al alloy by limiting the phase composition of the Zr-Ti-Mo-Nb-Al alloy to the BCC phase, and can increase the strength of the Zr-Ti-Mo-Nb-Al alloy by limiting the phase composition of the Zr-Ti-Mo-Nb-Al alloy to the B2 phase.
[0032] In the present invention, the phase composition of the Zr-Ti-Mo-Nb-Al alloy includes 60-65% BCC phase and 35-40% B2 phase by volume percentage.
[0033] In the present invention, the phase composition of the Zr-Ti-Mo-Nb-Al alloy preferably includes 60-65% BCC phase, more preferably 62% BCC phase, by volume percentage. The present invention further ensures high plasticity of the Zr-Ti-Mo-Nb-Al alloy by limiting the BCC phase content of the Zr-Ti-Mo-Nb-Al alloy.
[0034] In the present invention, the phase composition of the Zr-Ti-Mo-Nb-Al alloy preferably includes 35-40% of the B2 phase dispersed in the BCC phase, and more preferably 38% of the B2 phase, by volume percentage. The present invention further ensures the high strength of the Zr-Ti-Mo-Nb-Al alloy by limiting the B2 phase content of the Zr-Ti-Mo-Nb-Al alloy.
[0035] In the present invention, the size of the B2 phase is preferably 160 to 240 nm, and more preferably 180 to 200 nm. The present invention further improves the strength of the Zr-Ti-Mo-Nb-Al alloy by limiting the size of the B2 phase.
[0036] The present invention increases the strength of the Zr-Ti-Mo-Nb-Al alloy by adding Al and Zr and limiting their mass percentages to form a B2 phase; and improves the strength of the Zr-Ti-Mo-Nb-Al alloy by adding Ti, Mo, and Nb and limiting their mass percentages to regulate the proportion of the plastic BCC phase and the high-strength B2 phase in combination with Al.
[0037] The present invention also provides a method for preparing the Zr-Ti-Mo-Nb-Al alloy described in the above technical solution, comprising the following steps:
[0038] After the alloy raw materials are mixed, they are melted and hot isostatically pressed in sequence to obtain a Zr-Ti-Mo-Nb-Al alloy.
[0039] In the present invention, the alloy raw materials preferably include sponge titanium, sponge zirconium, Al-Mo master alloy and Al-Nb master alloy.
[0040] In the present invention, the purity of the titanium sponge is preferably 99%; the particle size of the titanium sponge is preferably 10-15 mm, more preferably 12 mm. The present invention limits the purity and particle size of the titanium sponge to ensure that the Ti source can be more fully mixed with other alloy raw materials.
[0041] In the present invention, the Al-Mo master alloy is preferably AlMo70 alloy. The present invention uses Al-Mo master alloy as raw material, which can balance the melting points of Mo and Al, avoid burning of Al element, and reduce the melting point difference between Mo and other alloy raw materials, which helps to mix the alloy raw materials evenly.
[0042] In the present invention, the purity of the AlMo70 alloy is preferably 99.9%; the particle size of the AlMo70 alloy is preferably less than 6.5 mm, more preferably 4 mm; the mass of Mo in the AlMo70 alloy is 65-75% of the total mass of the AlMo70 alloy, more preferably 70%. The present invention limits the purity, particle size and mass content of Mo in the AlMo70 alloy to ensure that the Mo source can be more fully mixed with other alloy raw materials.
[0043] In the present invention, the Al-Nb master alloy is preferably AlNb75 alloy. The present invention uses Al-Nb master alloy as raw material, which can balance the melting points of Nb and Al, avoid burning of Al element, and reduce the melting point difference between Nb and other alloy raw materials, which helps to mix the alloy raw materials evenly, thereby improving the plasticity of Zr-Ti-Mo-Nb-Al alloy.
[0044] In the present invention, the purity of the AlNb75 alloy is preferably 99.9%; the particle size of the AlNb75 alloy is preferably less than 6 mm, more preferably 4 mm; the mass of Nb in the AlNb75 alloy is 74-76% of the total mass of the AlNb75 alloy, more preferably 75%. The present invention limits the purity, particle size and mass content of the AlNb75 alloy to ensure that the Nb source can be more fully mixed with other alloy raw materials.
[0045] In the present invention, the purity of the sponge zirconium is preferably 99.9%; the particle size of the sponge zirconium is preferably 10-15 mm, more preferably 12 mm. The present invention limits the purity and particle size of the sponge zirconium to ensure that the Zr source can be more fully mixed with other alloy raw materials.
[0046] The present invention has no special limitation on the mixing of the alloy raw materials, and any mixing method known in the art can be used.
[0047] In the present invention, the smelting preferably includes vacuum consumable arc melting and vacuum consumable shell melting performed sequentially.
[0048] In the present invention, the temperature of the vacuum consumable arc melting is preferably 1700-1900°C; the melting time is preferably 5-8 minutes; the melting power is preferably not less than 380kW; and the melting pressure is preferably 8-15kPa. The present invention melts the alloy raw material into liquid by limiting the parameters of the vacuum consumable arc melting, so that the alloy elements are more fully mixed.
[0049] In the present invention, the power of the vacuum consumable shell smelting is preferably 200-250kW; the time of the vacuum consumable shell smelting is preferably 5-8min; the pressure of the vacuum consumable shell smelting is preferably 8-15kPa; the number of vacuum consumable shell smelting is preferably 3-5 times. The present invention further mixes the alloy elements evenly by limiting the parameters of the vacuum consumable shell smelting.
[0050] After vacuum consumable shell smelting, the present invention preferably casts the product after vacuum consumable shell smelting. The present invention has no special limitation on the casting method, and the casting method well known in the art can be used.
[0051] In the present invention, the temperature of the hot isostatic pressing is preferably 700-750°C; the pressure of the hot isostatic pressing is preferably 100-140MPa, more preferably 120MPa; the time of the hot isostatic pressing is preferably 2-2.5h. The present invention further improves the density of the Zr-Ti-Mo-Nb-Al alloy by limiting the parameters of the hot isostatic pressing, and can promote the precipitation of the B2 phase in the alloy elements, forming an ultra-fine size B2 phase to significantly improve the mechanical properties of the alloy casting.
[0052] In the present invention, the hot isostatic pressing is preferably performed under an argon atmosphere.
[0053] The invention prepares a Zr-Ti-Mo-Nb-Al alloy having high strength and good plasticity by mixing alloy raw materials, melting them in sequence, converting the alloy into liquid, mixing them thoroughly, and then performing hot isostatic pressing to improve the compactness of the Zr-Ti-Mo-Nb-Al alloy.
[0054] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0055] Example 1
[0056] A Zr-Ti-Mo-Nb-Al alloy, wherein the components are, by mass percentage, 26.2% Ti, 5% Mo, 5% Nb, 3.8% Al and 60% Zr; by volume percentage, 61.94% BCC phase and 38.06% B2 phase with a size of 160 to 240 nm; the density of the Zr-Ti-Mo-Nb-Al alloy is 5.704 g / cm 3 .
[0057] The preparation method of the Zr-Ti-Mo-Nb-Al alloy is as follows: 3.8 The alloy components are calculated by mass percentage and the purity is 99% and the particle size is 10-15mm sponge zirconium, the purity is 99.9% and the particle size is 10-15mm sponge titanium, the purity is 99% and the particle size is 0-6.5mm AlMo70 alloy and the purity is 99.9% and the particle size is 0-6mm AlNb75 alloy are mixed and pressed into a consumable electrode, and melted in an argon atmosphere at a temperature of 1700°C, a power of 380kW and a pressure of 10kPa in a vacuum consumable arc melting for 6min, and then placed in an argon atmosphere in a vacuum consumable shell melting furnace with a power of 200-250kW and a pressure of 10kPa for 5min. After melting 3 times, pouring is performed, and then cooling with the furnace for 30min, taking out, and hot isostatic pressing is performed in an argon atmosphere to obtain Zr-Ti-Mo-Nb-Al 3.8 alloy; the hot isostatic pressing temperature is 700°C; the hot isostatic pressing pressure is 120MPa; the hot isostatic pressing time is 2h.
[0058] The Zr-Ti-Mo-Nb-Al prepared in Example 1 was analyzed by X-ray diffractometer. 3.8 The alloy was analyzed for phase composition and obtained as Zr-Ti-Mo-Nb-Al 3.8 The XRD pattern of the alloy is as follows Figure 1 As shown in the figure, superlattice diffraction peaks appear at around 2θ of 25° and 60°, indicating the existence of B2 phase; at 2θ of 36° to 39°, the diffraction peak broadens, indicating that the constituent phase is a dual phase. This shows that the Zr-Ti-Mo-Nb-Al prepared in Example 1 3.8 The alloy has BCC and B2 phase structures.
[0059] The Zr-Ti-Mo-Nb-Al prepared in Example 1 was observed by scanning electron microscopy. 3.8 The alloy was subjected to backscattered electron imaging, and SEM backscattered images with a magnification of 200 and a magnification of 3000 were obtained, as shown in FIG. Figure 2 and Figure 3As shown in the figure, the Zr-Ti-Mo-Nb-Al 3.8 The alloy matrix structure is a disordered BCC phase, and nanoscale precipitates, namely B2 phase, are dispersed in the matrix.
[0060] The Zr-Ti-Mo-Nb-Al prepared in Example 1 was tested by Instron 5985 universal testing machine. 3.8 The alloy was subjected to room temperature quasi-static compression test. The test results are as follows Figure 4 As shown in the figure, the Zr-Ti-Mo-Nb-Al 3.8 The room temperature quasi-static compressive yield strength of the alloy is 1790 MPa, and the compressive failure strain is 16.75%.
[0061] The Zr-Ti-Mo-Nb-Al prepared in Example 1 was tested by using a split Hopkinson pressure bar dynamic mechanical properties test system. 3.8 The alloy was subjected to room temperature dynamic compression test. The test results are as follows Figure 5 As shown in the figure, the Zr-Ti-Mo-Nb-Al 3.8 The dynamic compressive strength of the alloy is 2712MPa, and the compression failure strain is 3.69%.
[0062] Example 2
[0063] A Zr-Ti-Mo-Nb-Al alloy, wherein the components are, by mass percentage, 29.7% Ti, 3% Mo, 3% Nb, 2.3% Al and 62% Zr; by volume percentage, 64.08% BCC phase and 35.92% B2 phase with a size of 160 to 240 nm; the density of the Zr-Ti-Mo-Nb-Al alloy is 5.686 g / cm 3 .
[0064] The preparation method of the Zr-Ti-Mo-Nb-Al alloy is as follows: 2.3The mass percentage of the alloy components is calculated to be 99% purity and 10-15mm sponge zirconium, 99.9% purity and 10-15mm sponge titanium, 99% purity and 0-6.5mm AlMo70 alloy and 99.9% purity and 0-6mm AlNb75 alloy. The mixture is pressed into a consumable electrode, and then melted in an argon atmosphere at a temperature of 1700°C, a power of 380kW, and a pressure of 10kPa in a vacuum consumable arc melting furnace for 5min, and then placed in an argon atmosphere in a vacuum consumable shell melting furnace with a power of 200-250kW and a pressure of 10kPa for melting for 5min. After melting three times, pouring is performed, and then cooling with the furnace for 30min, taking out, and hot isostatic pressing is performed in an argon atmosphere to obtain Zr-Ti-Mo-Nb-Al 2.3 alloy; the hot isostatic pressing temperature is 700°C; the hot isostatic pressing pressure is 120MPa; the hot isostatic pressing time is 2h.
[0065] Example 3
[0066] A Zr-Ti-Mo-Nb-Al alloy, wherein the components are, by mass percentage, 20.9% Ti, 8% Mo, 8% Nb, 6.1% Al and 57% Zr; by volume percentage, 62.36% BCC phase and 37.64% B2 phase with a size of 160 to 240 nm; the density of the Zr-Ti-Mo-Nb-Al alloy is 5.729 g / cm 3 .
[0067] The preparation method of the Zr-Ti-Mo-Nb-Al alloy is as follows: 6.1 The mass percentage of the alloy components is calculated to be 99% purity and 10-15mm sponge zirconium, 99.9% purity and 10-15mm sponge titanium, 99% purity and 0-6.5mm AlMo70 alloy and 99.9% purity and 0-6mm AlNb75 alloy. The mixture is pressed into a consumable electrode, and is melted for 7 minutes in a vacuum consumable arc melting furnace at a temperature of 1700°C, a power of 380kW and a pressure of 10kPa under an argon atmosphere, and then placed in a vacuum consumable shell melting furnace with a power of 200-250kW and a pressure of 10kPa under an argon atmosphere for 6 minutes. After melting three times, it is poured, and then cooled with the furnace for 30 minutes, taken out, and hot isostatically pressed under an argon atmosphere to obtain Zr-Ti-Mo-Nb-Al 6.1 alloy; the hot isostatic pressing temperature is 700°C; the hot isostatic pressing pressure is 120MPa; the hot isostatic pressing time is 2h.
[0068] The Zr-Ti-Mo-Nb-Al prepared in Examples 2 to 3 was analyzed by X-ray diffractometer. 3.8 The alloy was subjected to phase composition analysis, and the X-ray diffractometer experimental results showed that the Zr-Ti-Mo-Nb-Al 2.3 The alloy has BCC and B2 phase structures.
[0069] The Zr-Ti-Mo-Nb-Al prepared in Example 2 was tested using an Instron 5985 universal testing machine. 2.3 Alloy and Zr-Ti-Mo-Nb-Al prepared in Example 3 6.1 The alloy was subjected to a room temperature quasi-static compression test. The results of the room temperature quasi-static compression test showed that the Zr-Ti-Mo-Nb-Al 2.3 The room temperature quasi-static compressive yield strength of the alloy is 1670 MPa, and the compressive failure strain is 15.91%. The Zr-Ti-Mo-Nb-Al 6.1 The room temperature quasi-static compressive yield strength of the alloy is 1729 MPa, and the compressive failure strain is 16.04%.
[0070] The Zr-Ti-Mo-Nb-Al prepared in Example 2 was tested by using a split Hopkinson pressure bar dynamic mechanical properties test system. 2.3 Alloy and Zr-Ti-Mo-Nb-Al prepared in Example 3 6.1 The alloy was subjected to a room temperature dynamic compression test. The results of the room temperature dynamic compression test showed that the Zr-Ti-Mo-Nb-Al 2.3 The dynamic compressive strength of the alloy is 2515MPa, and the compression failure strain is 3.64%; the Zr-Ti-Mo-Nb-Al prepared in Example 3 6.1 The dynamic compressive strength of the alloy is 2653MPa, and the compression failure strain is 3.69%.
[0071] It can be seen from the above experimental results that the Zr-Ti-Mo-Nb-Al alloy provided by the present invention has high strength and good plasticity.
[0072] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A Zr-Ti-Mo-Nb-Al alloy, wherein the components are as follows by mass percentage: Ti 20-30%, Mo 3-8%, Nb 3-8%, Al 2-8% and the balance Zr.
2. The Zr-Ti-Mo-Nb-Al alloy according to claim 1, characterized in that: The components are calculated by mass percentage as follows: Ti 24-28%, Mo 4-6%, Nb 4-6%, Al 3-7% and the balance Zr.
3. The Zr-Ti-Mo-Nb-Al alloy according to claim 1 or 2, characterized in that: The phase composition of the Zr-Ti-Mo-Nb-Al alloy includes a BCC phase and a B2 phase dispersed in the BCC phase.
4. The Zr-Ti-Mo-Nb-Al alloy according to claim 3, characterized in that: The phase composition of the Zr-Ti-Mo-Nb-Al alloy includes 60-65% of BCC phase and 35-40% of B2 phase by volume percentage.
5. The method for preparing the Zr-Ti-Mo-Nb-Al alloy according to any one of claims 1 to 4, comprising: After the alloy raw materials are mixed, they are melted and hot isostatically pressed in sequence to obtain a Zr-Ti-Mo-Nb-Al alloy.
6. The preparation method according to claim 5, characterized in that: The alloy raw materials include sponge titanium, sponge zirconium, Al-Mo master alloy and Al-Nb master alloy.
7. The preparation method according to claim 5, characterized in that: The smelting includes vacuum consumable arc melting and vacuum consumable shell melting which are carried out in sequence.
8. The preparation method according to claim 7, characterized in that: The temperature of the vacuum consumable arc melting is 1700-1900° C., and the time of the vacuum consumable arc melting is 5-8 minutes.
9. The preparation method according to claim 7, characterized in that: The power of the vacuum consumable shell smelting is 200-250 kW, and the time of the vacuum consumable shell smelting is 5-8 minutes.
10. The preparation method according to claim 5, characterized in that: The temperature of the hot isostatic pressing is 700-750° C., the pressure of the hot isostatic pressing is 100-140 MPa, and the time of the hot isostatic pressing is 2-2.5 hours.